A webbased intervention for patients with an implantable cardioverter defibrillator, a qualitative study of nurses experiences. (19th May 2022) - Helmark, C; Egholm, CL; Rottmann, N; Skovbakke, SJ; Johansen, JB; Nielsen, JC; Larroude, CE; Riahi, S; Brandt, CJ; Pedersen, SS
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Implantable cardioverter defibrillator (ICD) therapy is the gold standard for prevention of sudden cardiac death. Patients generally adapt well to living with an ICD, but 20% have difficulties adjusting, with increased risk of anxiety and depression and decreased quality of life. New web-based interventions engaging patients with an ICD might be efficient, but there is sparse knowledge on experiences with web-based care from the perspective of cardiac nurses. Purpose: The aim of the study was to explore cardiac nurses' experiences with a web-based intervention designed to empower patients with an ICD. Methods: We conducted a qualitative study based on semi-structured interviews. The informants (n=9) were experienced cardiac nurses across 5 Danish university hospitals. They were delivering a comprehensive web-based intervention for patients with an ICD, including patient education, chats, monitoring of anxiety and depression and a patient forum. The intervention was tested in a randomized controlled trial. The interviews were transcribed verbatim, coded and analyzed using qualitative content analysis with NVivo software. Results: We identified an overall theme: "Between traditional nursing and modern eHealth". The theme emerged from six categories, each covering three or four subcategories (Figure 1). The categories were: (1) comprehensive intervention, (2) patient-related differences in engagement, (3) following the protocol is a balancing act, (4) online communication challenges patient contact, (5) professional collaboration varies, and (6) an intervention with potential. Cardiac nurses were in general positive towards the concept of this web-based intervention and believe it holds a large potential. On the other hand, they were challenged by not establishing a personal relation and by losing face-to-face contact with patients, which they found valuable for getting a feeling for patients' wellbeing and potential mental health issues. Ensuring face-to-face contact by either starting the intervention with a personal contact or including the possibility of video contacts might enhance the value of web-based interventions from the perspective of cardiac nurses. The nurses found the intervention especially suitable for patients who had suffered a cardiac arrest. Conclusion: Specific training in eHealth communication is necessary as web-based care entails a shift in nursing role and a new format of communication for cardiac nurses. Future evaluations of web-based cardiac rehabilitation interventions in clinical practice are needed to assess the potential impact in "real-life" cardiac care.